1963
DOI: 10.1128/jb.86.5.1025-1029.1963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moderate Temperature on Growth and Malic Dehydrogenase Activity of a Marine Psychrophile

Abstract: MORITA, RICHARD Y. (Oregon State University, Corvallis), AND SHERIL D. BURTON. Influence of moderate temperature on growth and malic dehydrogenase activity of a marine psychrophile. J. Bacteriol. 86:1025-1029. 1963.-The maximal and optimal growth temperatures for a marine psychrophilic vibrio (PS 207) were determined to be 30 and 24.5 C, respectively. Malic dehydrogenase was found to be functioning in whole cells at about JWo of its observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1963
1963
1979
1979

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 9 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…It is entirely possible that the wild type, as represented by the ATCC culture, cannot synthesize the enzyme system or synthesizes 2,680 a portion that is inactivated at elevated tempera-0 ture and that the selective pressures of the aquatic 2,860 environment allow a particular mutant popula-2,500 tion to survive. This hypothesis is consistent with observations of Peterson and Gunderson (20) and Morita and Burton (16). It is also reasonable to suggest that a formic hydrogenlyase 23,30 system active at an elevated temperature may be 2,250 irreversibly lost upon prolonged storage as are 2,260 virulence factors of certain pathogenic organisms.…”
supporting
confidence: 90%
“…It is entirely possible that the wild type, as represented by the ATCC culture, cannot synthesize the enzyme system or synthesizes 2,680 a portion that is inactivated at elevated tempera-0 ture and that the selective pressures of the aquatic 2,860 environment allow a particular mutant popula-2,500 tion to survive. This hypothesis is consistent with observations of Peterson and Gunderson (20) and Morita and Burton (16). It is also reasonable to suggest that a formic hydrogenlyase 23,30 system active at an elevated temperature may be 2,250 irreversibly lost upon prolonged storage as are 2,260 virulence factors of certain pathogenic organisms.…”
supporting
confidence: 90%
“…In spite of protection of the enzyme by the whole cell (Morita and Burton, 1963), malic dehydrogenase is sensitive to 30 C and may contribute to the inability of this psychrophile to grow above this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Burton and Morita (15) found that 55 to 60% of the malic dehydrogenase activity of cellfree extracts of a marine facultative psychrophile (optimal temperature for growth, 24 C; maximal, 30 C) was lost by exposure of the extract to 30 C for 15 min. The rate of denaturation of the enzyme was much greater at 35 and 40 C. Heat stability of the enzyme was found to be greater in whole cells than in cell-free extracts (56). Heating the cells or treatment with a lysing agent apparently destroyed some regulatory factor for malic dehydrogenase activity.…”
Section: Other Factorsmentioning
confidence: 93%